Programming in BASIC - Lampton, Christopher (New York ; Sydney : Franklin Watts, 1990)
This book introduces the computer program language known as Basic, which was originally developed as a tool for teaching computer programming, but may also be used for writing extremely sophisticated programs.
Includes index.
II 15/01/2019
Loans
Keywords: BASIC (Computer program language); Programming languages (Computers); Computers